Anne Ubersfeld: L'école du spectateur, Lire le théâtre 2, Paris, Editions sociales, 1981, 352 p. Keir Elam: The semiotics of Theatre and Drama, London and New York, Methuen, 1980, XII + 248 p. Patrice Pavis: Dictionnaire du théâtre, Paris, Editions sociales, 1980, 482 p. - Jansen, Steen (Revue Romane, 1982)
no abstract